2015
DOI: 10.5664/jcsm.4844
|View full text |Cite
|
Sign up to set email alerts
|

All APAPs Are Not Equivalent for the Treatment of Sleep Disordered Breathing: A Bench Evaluation of Eleven Commercially Available Devices

Abstract: Large differences between APAP devices in the treatment efficacy and the accuracy of report were evidenced in the current study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…Five devices increased pressure during snoring and seven devices increased pressure during central apneas. Only five of the APAP machines studied achieved treatment efficacy of >90 %, and seven devices accurately identified AHI >90 % of the time [8]. These studies illustrate the variance between devices in event detection and response algorithm.…”
Section: Auto-adjusting Pap General Principlesmentioning
confidence: 87%
“…Five devices increased pressure during snoring and seven devices increased pressure during central apneas. Only five of the APAP machines studied achieved treatment efficacy of >90 %, and seven devices accurately identified AHI >90 % of the time [8]. These studies illustrate the variance between devices in event detection and response algorithm.…”
Section: Auto-adjusting Pap General Principlesmentioning
confidence: 87%
“…Each residual event was scored by considering both the amplitude reduction and the corresponding duration, i.e., ΔV' ≤ 10% of baseline: apnea; 10% < ΔV' ≤ 70%: hypopnea, with a duration ≥ 10 sec. [25][26][27] In addition, the AHI, AI, and pressure data on the device report were also noted for comparison. Results were averaged on two tests for fixed CPAP and on three tests for APAP.…”
Section: Discussionmentioning
confidence: 99%
“…Bench studies have been proposed to evaluate the responses of APAP devices in different conditions, such as the presence of predefined sleep disordered breathing (SDB) patterns and air leak, [18][19][20][21][22][23][24][25] whereas no such study to date has focused on pressure-relief CPAPs and APAPs. We investigated seven pressure-relief features developed by three CPAP device manufacturers with a previously reported bench model.…”
Section: 17mentioning
confidence: 99%
See 1 more Smart Citation
“…An issue of concern that arises from these observations is that if patients exhibiting NED actually have different upper airway physiology or exhibit upper airway muscle dysfunction, would they require different positive-pressure devices or electrical stimulation modalities than currently available. It also follows that bench tests used to evaluate CPAP devices based on the Starling resistor model would not apply to all patients (1,6,17,22,38). Recently, Lambeth et al (20) published a paper that observed NED within a collapsible tube model using a unidirectional flow source.…”
Section: Introductionmentioning
confidence: 99%